T-shirt quilts - Causee, Linda (Leisure Arts, Inc., 2013)
Turn those treasured t-shirts into something useful again! Causee shows you how to make unique quilts or wall hangings that celebrate your favorite sporting events, concerts, vacation spots, and other themes!